Development and Quality Assessment of Mango Peel Powder Incorporated Functional Carabeef Cookies - M, M. Goswami; Sharma, B. D.; Mendiratta, S. K.; Pathak, V.; Kumar, R. R.; Talukdar, S. (Journal of Meat Science, 2017)
The present study was carried out to develop and assess the quality attributes of fiber enriched functional carabeeef cookies. The products were formulated with incorporation of mango peel powder (MPP) by replacing refined wheat flour as: Control (C) with no mango peel powder, MT1 (with 5% MPP), MT2 (with 10% MPP) and MT3 (with 15% MPP). There was a significant difference (p<0.05) in all physcio-chemical properties due to incorporation of MPP in carabeef cookies. The cooking yield and moisture content significantly increased (p<0.05), however, protein and ash content decreased significantly (p<0.05) at more than 10% level. Mean insoluble dietary fiber (IDF), soluble dietary fiber (SDF) and total dietary fiber (TDF) content increased significantly (p<0.05) with the incorporation of MPP in carabeef cookies. Spread ratio and thickness of cookies were comparable with control upto 10% level however, decreased significantly (p<0.05) at 15% of mango peel powder incorporation. The sensory scores for all attributes were comparable upto 10% level of MPP incorporation. The sensory scores decreased significantly (p<0.05) at 15% MPP level than control except for texture. Shear force value and adhesiveness were not affected upto 10% MPP incorporation, but decreased significantly (p<0.05) at 15% level. Color parameters like redness, yellowness, chroma and hue angles values were not significantly affected. Thus mango peel powder at 10% level was selected as optimum for incorporation in carabeef cookies as natural fiber source.